Volumetric Body Mass Estimate and in vivo Reconstruction of the Russian Pareiasaur Scutosaurus karpinskii - Romano, Marco; Manucci, Fabio; Rubidge, Bruce; Van den Brandt, Marc J. (Frontiers in Ecology and Evolution, 2021)
Pareiasaurs (Amniota, Parareptilia) were characterized by a global distribution during the Permian period, forming an important component of middle (Capitanian) and late Permian (Lopingian) terrestrial tetrapod biodiversity. This clade includes some of the first large-sized terrestrial herbivores, playing a fundamental role in the structure of middle and late Permian biodiversity and ecosystems. Despite their important ecological role and relative abundance around the world, our general knowledge of the biology of these extinct tetrapods is still quite limited. In this contribution we provide a possible in-vivo reconstruction of the largest individual of the species Scutosaurus karpinskii and a volumetric body mass estimate for the taxon, considering that body size is one of the most important biological aspects of organisms. The body mass of Scutosaurus was calculated using a 3D photogrammetric model of the complete mounted skeleton PIN 2005/1537 from the Sokolki locality, Arkhangelsk Region, Russia, on exhibit at the Borissiak Paleontological Institute, Russian Academy of Sciences (Moscow). By applying three different densities for living tissues of 0.99, 1 and 1.15 Kg/1000 cm3 to the a reconstructed ‘slim’, ‘average’ and ‘fat’ 3D models we obtain an average body mass respectively of 1060, 1160 and 1330 Kg, with a total range varying from a minimum of one ton to a maximum of 1.46 tons. Choosing the average model as the most plausible reconstruction and close to the natural condition, we consider a body mass estimate of 1160 Kg as the most robust value for Scutosaurus, a value compatible with that of a large terrestrial adult black rhino and domestic cow. This contribution demonstrates that barrel-shaped herbivores, subsisting on a high-fibre diet and with a body mass exceeding a ton, had already evolved in the upper Palaeozoic within parareptiles, shedding new light on the structure of the first modern terrestrial ecosystems.